Novel Low-Complexity CCK Decoder for IEEE 802.11b System - Tuyen, Ta Duc; Vu, Trinh Anh (VNU Journal of Science: Natural Sciences and Technology, 2011)
Abstract . A novel low-complexity decoder for Complementary Code Keying (CCK) modulation is proposed in this study. Compared to the decoder architecture based on Fast Walsh Transform (FWT), the presented architecture requires less resource on hardware and still keeps reasonable performance of system. By mapping complex chips to modulo-4 numbers and decomposing coded words by in-dependent angle parameters based on theirs different properties, the proposed method allows a faster and more direct decoding for those parameters than traditional method. Keywords: CCK, FWT, IEEE 802.11b